A classificação das disciplinas matemáticas e a Mathesis Universalis nos séculos XVI e XVII: um estudo do pensamento de Adriaan van Roomen - Oliveira, Zaqueu Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
During the sixteenth and seventeenth centuries we can find many studies on the classification of disciplines, their specifities and differences. Scholars of this period as Petrus Ramus (1515-1572), Christoph Clavius (1538-1612), Adriaan van Roomen (1561- 1615) and Francis Bacon (1561-1626) not only dedicated to sort, organize and prioritize those disciplines they denominated of mathematical disciplines, but also to study the nature of mathematical knowledge in order to understand if the type of statement made by mathematical disciplines produced a certain and indubitable knowledge, and to establish relatioships with other áreas, specially with philosophy. in this thesis, I analyse the work Universae Mathesis Idea (1602) and the liber pirmus of Mathesis Polemica (1605), wich contain a short description of the eighteen disciplines wich van Roomen calls mathematics. Such disciplines are divided into two groups: the principal mathematics wich are subdivided into pure mathematics (logistics, prima mathesis, arithmetic, and geometry) and mixed mathematics (astronomy, uranography, chronology, cosmography, geography, chorography, topography, topothesis, astrology, geodesy, music, optics, and euthymetria); and mechanical mathematics (sphaeropoeia, manganaria, mechanopoetica, organopoetica, and thaumatopoetica) that are related to the use and construction machinery, a subject that is directly related to mathematics instrumentation, which developed quite period. The author also presentes a brief chapter about the subjects he calls the almost mathematics. The description of van Roomen's mathematical disciplines includes among other things, the object of study, the principles, the place in relation to other disciplines and the usefulness of each. Seek contributions to studies on the life and work of van Roomen, and also try to understand some aspects of the philosophical status of mathematics at the time. Furthermore, I am ...

Durante os séculos XVI e XVII é possível encontrar diversos estudos acerca da classificação das disciplinas, suas especificidades e diferenças. Pensadores desse período como Petrus Ramus (1515-1572), Christoph Clavius (1538-1612), Adriaan van Roomen (1561-1615) e Francis Bacon (1561-1626) se debruçaram sobre o tema não somente para classificar, organizar e hierarquizar aquelas disciplinas que eles denominavam de disciplinas matemáticas, mas também para estudar a natureza do conhecimento matemático buscando compreender se o tipo de demonstração realizada pelas disciplinas matemáticas produzia um conhecimento certo e indubitável, além de estabelecer relações com outras áreas, principalmente com a filosofia. Neste trabalho, analiso a obra Universae Mathesis Idea (1602) e o liber primus da Mathesis Polemica (1605), as quais contêm uma pequena descrição das dezoito disciplinas que van Roomen denomina de matemáticas. Tais disciplinas estão divididas em dois grupos: as matemáticas principais que são subdivididas em matemáticas puras (logística, prima mathesis, aritmética e geometria) e mistas (astronomia, uranografia, cronologia, cosmografia, geografia, corografia, topografia, topothesis, astrologia, geodesia, música, óptica e euthymetria); e as matemáticas mecânicas (sphaeropoeia, manganaria, mechanopoetica, organopoetica e thaumatopoetica) que estão relacionadas ao uso e construção de máquinas, assunto que está diretamente relacionado à instrumentação matemática, que se desenvolveu bastante naquele período. O autor traz ainda um breve capítulo sobre as disciplinas que ele nomeia de quase matemáticas. A descrição das disciplinas matemáticas de van Roomen inclui dentre outras coisas, o objeto de estudo, os princípios, o lugar em relação às demais disciplinas e a utilidade de cada uma. Buscarei não somente contribuições para estudos sobre a vida e obra de van Roomen, mas também...
Keywords: Romain, Adrien, 1561-1615; Matemática - História - Séc. XVI; Matemática - História - Séc. XVII; Matemática - Classificação; Mathematics - History